2013
DOI: 10.1158/1078-0432.ccr-13-1121
|View full text |Cite
|
Sign up to set email alerts
|

Cidofovir: A Novel Antitumor Agent for Glioblastoma

Abstract: Purpose Cidofovir (CDV) is a FDA approved nucleoside antiviral agent used to treat severe human cytomegalovirus (HCMV) infection. Until now, no clear therapeutic effects of CDV have been reported outside of the setting of viral infection, including a potential role for CDV as an antineoplastic agent for the treatment of brain tumors. Experimental Design We investigated CDV cytotoxicity against glioblastoma (GBM) cells, U87MG and primary SF7796, in vitro and in vivo, using an intracranial xenograft model. Sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 37 publications
1
52
0
2
Order By: Relevance
“…Recently, these findings were confirmed by P. Hadaczek and co-workers who also found that CDV is incorporated into cellular DNA activating DNA damage response pathways due to increased DNA breaks that prompt elevated tumor cell apoptotic response in glioblastoma cells (Hadaczek et al, 2013).…”
Section: Why Is CDV Selective Against Hpv-induced Hyperproliferation?mentioning
confidence: 65%
“…Recently, these findings were confirmed by P. Hadaczek and co-workers who also found that CDV is incorporated into cellular DNA activating DNA damage response pathways due to increased DNA breaks that prompt elevated tumor cell apoptotic response in glioblastoma cells (Hadaczek et al, 2013).…”
Section: Why Is CDV Selective Against Hpv-induced Hyperproliferation?mentioning
confidence: 65%
“…The drug potentiated the effects of radiation, but the mechanism was not dependent on HCMV. 31 Thus, antiviral therapy may be a promising alternative for treating patients with GBMs and may provide both anti-viral and off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent pre-clinical animal study on cidofovir, another anti-viral nucleoside analog [47]. Cidofovir synergized with irradiation in vitro independent of CMV infection status, and synergized with irradiation in animal glioblastoma models in the absence of CMV to give a significant survival benefit.…”
Section: More Controversy: CMV As a Therapeutic Target In Glioblastomamentioning
confidence: 77%
“…Indeed the NIH has recently proposed performing studies to validate key results [55], and this type of argument could be resolved by such a process. The valganciclovir question can only be resolved by conducting a randomized trial, and effects of valganciclovir on standard therapies should also be evaluated, as this may influence conventional therapies as was shown for the anti-viral agent cidofovir [47].…”
Section: Discussionmentioning
confidence: 99%